2019
DOI: 10.1016/j.pbi.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting genetic variation in nitrogen use efficiency for cereal crop improvement

Abstract: Highlights A statement on the critical importance of this area of plant science in terms of food security and sustainability. An outline of the critical NUE processes and example studies of identified variation in the complex trait of nitrogen use efficiency. Reference to number of critical single key genes/alleles which have major impacts on NUE. A description of the most useful genetic approaches being utilised to breed for NUE in cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
89
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 60 publications
1
89
0
1
Order By: Relevance
“…Thus, an integrated soil-crop system management strategy could help to improve grain yield and NUE as proposed by Meng et al [65]. Hawkesford et al [66] reported that 33% of applied N fertilizer is recovered in the harvested grain. Thus, 67% of N is lost, which could be a major source of pollutants and should be a major target for crop improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an integrated soil-crop system management strategy could help to improve grain yield and NUE as proposed by Meng et al [65]. Hawkesford et al [66] reported that 33% of applied N fertilizer is recovered in the harvested grain. Thus, 67% of N is lost, which could be a major source of pollutants and should be a major target for crop improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a split application of N resulted in higher N efficiencies, i.e., NUE, nitrogen uptake efficiency, and nitrogen utilization efficiency at all sites for both years. Thus, the idea of Hawkesford et al [66] to recover maximum applied N fertilizer is possible through its split application during different stages of the crop. Furthermore, a split application of N resulted in the maximum agronomic traits, and a significant combined strong relationship was obtained between grain yield and crop physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…NUE is a complex trait affected by both genetic and environmental factors [22]. It is composed of two main components, N uptake efficiency (NUpE) and N utilization efficiency (NUtE), which are influenced by biochemistry, phenology, and architecture, as well as the external environment such as N availability [23,24]. Studies have shown the role of total plant dry matter, nitrogen absorption, and root morphological traits in improving NUE [19,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Considering all results, it is suggested that both total N content and NO 3 − concentration may not be the major factors responsible for the higher chlorophyll content in Scout 66, while the signal derived from the NO 3 − concentration changing could play a critical role in affecting chlorophyll metabolism. Nitrogen absorption efficiency and N utilization efficiency are important indexes to evaluate the N use efficiency of plants, which were influenced by roots and shoots biomass, architecture, and responses to the deficiency nourishment environment [31,32]. Initially N, which is rapidly utilized, is taken up via seedling roots and is important for early crop establishment.…”
Section: Discussionmentioning
confidence: 99%